Peripheral blood leukocyte signatures as biomarkers in relapsed ovarian cancer patients receiving combined anti‐CD73/anti‐PD‐L1 immunotherapy in arm A of the NSGO‐OV‐UMB1/ENGOT‐OV30 trial - Luka Tandaric; Annika Auranen; Katrin Kleinmanns; René DePont Christensen; Liv Cecilie Vestrheim Thomsen; Cara Ellen Wogsland; Emmet McCormack; Johanna Mäenpää; Kristine Madsen; Karen Stampe Petersson; Mansoor Raza Mirza; Line Bjørge (Molecular Oncology)
Immune checkpoint inhibitors have demonstrated limited efficacy in overcoming immunosuppression in patients with epithelial ovarian cancer (EOC). Although certain patients experience long‐term treatment benefit, reliable biomarkers for responder pre‐selection and the distinction of dominant immunosuppressive mechanisms have yet to be identified. Here, we used a 40‐marker suspension mass cytometry panel to comprehensively phenotype peripheral blood leukocytes sampled over time from patients with relapsed EOC who underwent combination oleclumab (anti‐CD73) and durvalumab (anti‐PD‐L1) immunotherapy in the NSGO‐OV‐UMB1/ENGOT‐OV30 trial. We found that survival duration was impacted by baseline abundances of total peripheral blood mononuclear cells. Longitudinal analyses revealed a significant increase in CD14+CD16− myeloid cells during treatment, with significant expansion of monocytic myeloid‐derived suppressor cells occurring in patients with shorter progression‐free survival, who additionally showed a continuous decrease in central memory T‐cell abundances. All patients demonstrated significant PD‐L1 upregulation over time on most T‐cell subsets. Higher CD73 and IDO1 expression on certain leukocytes at baseline significantly positively correlated with longer progression‐free survival. Overall, our study proposes potential biomarkers for EOC immunotherapy personalization and response monitoring; however, further validation in larger studies is needed.